The insignificance of GDP growth rate to people’s welfare: a political economy analysis of China’s impressive GDP - Asmarawati Handoyo; Yuli Isnadi (Department of Government Studies Universitas Muhammadiyah Makassar, 2023)
In recent decades, there was a fierce debate about whether Gross Domestic Product (GDP) accurately describe people’s welfare. This manuscript aims to prove, an impressive GDP does not mean that people live on welfare. This topic is important to be discussed, simply, because it shows the actual condition of the people during their impressive GDP growth, besides, theoretically, it also sheds light on the correlation between GDP and real welfare. Taking China between 1980-2014, when China experienced the highest GDP growth as a case study, this investigation used secondary data provided by previous empirical research documents and international organizations’ data such as UNDP, WHO, World Bank and other relevant sources. The data was analyzed by comparative research method for comparing China’s GDP rate with China’s achievement on five aspects of alternative economic development gauges: inequality rates, life expectancy, health quality, education attainment, and environmental impacts. This investigation figured out that the impressive of China’s GDP has no direct correlation to Chinese real welfare. Along with the impression of China’s GDP, the Chinese must deal with inequality, the low government budget for human resources development, and environmental issues. This finding might support the previous analysts who were pessimists about the accuracy of GDP in measuring people’s welfare and develop a new path for future research.